(untitled) (Pedagogy of Higher and Secondary Education, 2013)
Zelenkova N. I., Golodenko A. N. Project-based learning environment in. The article reveals the essence of the project method in achieving the goals of methodological. The essence of the project and stages of the work is described here. Causes the use of project-based learning, which contribute to the development of various features. Attention is paid to design and exploration activities during the use of which is solved a number of multi-level teaching, educational and developmental problems.